Determining the Appropriate Treatment for T-Cell Acute Lymphoblastic Leukemia With SET-CAN/NUP214 Fusion: Perspectives From a Case Report and Literature Review - Lin, Na; Liu, Zhenghua; Li, Yan; Yan, Xiaojing; Wang, Lei (Frontiers in Oncology, 2021)
SET-CAN/NUP214 fusion is a recurrent event most commonly seen in T-cell acute lymphoblastic leukemia (T-ALL). It is related to resistance to glucocorticoids and chemotherapy; however, the reported prognosis of T-ALL with SET-CAN/NUP214 fusion is diverse, and the optimal treatment option remains undetermined. Here, we present the treatment process of an illuminating case of T-ALL with SET-CAN/NUP214 fusion. The patient showed early resistance to routine VICLP chemotherapy (at 15th day, 79.2% blasts), but the leukemia burden was significantly reduced after 28-day induction chemotherapy (18.85% blasts), even though she still didn’t achieve complete remission (CR) after a second course of high-dose methotrexate (3 g/m2) and pegaspargase. Ex vivo drug sensitivity screening using a panel of 165 kinds of cytotoxic drugs, targeted therapy drugs, combination chemotherapy drugs, etc., was conducted on the refractory leukemia cells, which showed extensive resistance to various regimens. Surprisingly, AML-like scheme DAE scheme (daunorubicin + cytarabine + etoposide) and carfilzomib showed the highest ex vivo inhibition rate. The patient received DAE regimen chemotherapy, and finally achieved complete remission and received allogenic hematopoietic stem cell transplantation (allo-HSCT). According to our own findings and a literature survey, we found that T-ALL patients with SET-CAN/NUP214 fusion usually shows early resistance to chemotherapy, but they have a delayed response, and the CR rate is not compromised; thus, a chemotherapy regimen featuring a 28-day long course, such as that used in GRAALL 2003 or 2005, is recommended for induction therapy. For refractory patients, AML-like therapy such as DAE or CLAG in combination with asparaginase may be beneficial. In addition, carfilzomib may be a useful therapeutic drug and is worthy of further study. Allo-HSCT improves prognosis and we recommend HSCT if possible. Additional chromosomal or molecular events may affect the prognosis, and further investigation is needed. We believe that through proper treatment, the prognosis of patients with SET-CAN/NUP214 fusion can be greatly improved, at least not worse than that of other T-ALL patients.